Fluctuations of current, electroluminescence and acoustic emission in light-emitting А³В⁵ heterostructures - Vlasenko, A.I.; Lyashenko, O.V.; Oleksenko, P.F.; Veleschuk, V.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
It is shown, that in heterostructures based on A³B⁵ compounds acoustic emission occurrence, current and light fluctuations, evolution electroluminescence spectrums, current-voltage characteristics degradation occur simultaneously and has the common origin.